Contextual-Based Multimedia on Multiplication and Division to Enhance Students’ Conceptual Understanding - Pande Kadek Perdi Diantara; Gusti Ngurah Sastra Agustika; Komang Alit Wahyuni (Jurnal Media dan Teknologi Pendidikan, 2025)
Mathematics learning in elementary schools still faces challenges, especially in multiplication and division materials that are often difficult for students to understand conceptually. This study aims to develop and test the effectiveness of contextual-based multimedia in improving students' conceptual understanding of the material. The development model used is the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The subjects of the study were 22 fourth-grade elementary school students. The types of data used in this study are qualitative data and quantitative data. Data collection methods use several methods such as observation, interviews, questionnaires and tests. The instruments used are questionnaire sheets and multiple-choice tests. Data analysis techniques include quantitative and qualitative descriptive analysis. The results of the study indicate that the contextual-based multimedia developed is valid, practical, and effective in improving students' conceptual understanding. Students showed an increase in test scores and high learning engagement. The implications of this study indicate the importance of using media that link material to real life to create meaningful and contextual learning in elementary school mathematics classes.